2021
DOI: 10.1039/d0sc04379f
|View full text |Cite
|
Sign up to set email alerts
|

An explicitly designed paratope of amyloid-β prevents neuronal apoptosis in vitro and hippocampal damage in rat brain

Abstract: Herein, the therapeutic potentials of an explicitly designed peptide probe are systematically illuminated in vitro and in vivo against Aβ aggregation. The probe demonstrates remarkable potency for attenuating neurotoxicity and hippocampal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
1
4
0
Order By: Relevance
“…The protective behavior of N -Me-F , N -Me-L and N -Me-F/L counteracting cytotoxicity is expressed in the assay measuring caspase-3 activity, where they significantly decrease caspase-3 activation compared to the WT and partly to the control. This is in alignment with other N -methylated peptides in the literature 70 .…”
Section: Discussionsupporting
confidence: 89%
“…The protective behavior of N -Me-F , N -Me-L and N -Me-F/L counteracting cytotoxicity is expressed in the assay measuring caspase-3 activity, where they significantly decrease caspase-3 activation compared to the WT and partly to the control. This is in alignment with other N -methylated peptides in the literature 70 .…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies have elucidated the dock-lock mechanism of fibril formation, where unstructured Aβ monomers transiently associate with the fibril surface before undergoing a slower conformational rearrangement and incorporating into the primary fibril lattice. This process, involving the central K16-A21 and C-terminal M35-V40 regions, plays a critical role in fibrillation and presents a potential avenue for inhibiting amyloidosis. Remarkably, our recent investigation employing a synthetic paratope, SP1, has demonstrated selective binding to the LVFFA epitope, a crucial amyloidogenic region of Aβ peptide . Furthermore, SP1 effectively disaggregated preformed fibrils of Aβ40, leading to the formation of nontoxic species.…”
Section: Gxxxg Motif Targeted Inhibitorsmentioning
confidence: 97%
“…Remarkably, our recent investigation employing a synthetic paratope, SP1, has demonstrated selective binding to the LVFFA epitope, a crucial amyloidogenic region of Aβ peptide. 123 Furthermore, SP1 effectively disaggregated preformed fibrils of Aβ40, leading to the formation of nontoxic species. Solution NMR analysis revealed that SP1 disrupts the essential dock-lock interactions of monomeric Aβ, suggesting molecular interference in the critical domain.…”
Section: ■ Gxxxg Motif Targeted Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many materials have been employed to detoxify sulfur mustard and its analogous derivatives; in this context, owing to its attenable functionality, superior chemical and thermal stability, and enhanced porosity, POPs emerge as a judicious choice. 97 POPs are a class of advanced functional materials with structural tailorability, inherent porosity, and high flexibility, which have served for several applications like CO 2 capture, 98,99 CO 2 reduction to solar fuels, 100,101 biomass valorisation, 102,103 organic transformation reactions, 104,105 CO 2 fixation, 99 gas and liquid separation, 106 water purification, 107,108 energy storage, 109 chemo-and biosensing 110 and HD decontamination [111][112][113][114][115] etc. (Fig.…”
Section: •−mentioning
confidence: 99%